2019
DOI: 10.1177/1708538119881347
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of transcutaneous oxygen pressure in patients with post-thrombotic syndrome: Findings and possible clinical applications

Abstract: Objectives Post-thrombotic syndrome is the commonest long-term sequela of deep venous thrombosis. Severe post-thrombotic syndrome reduces importantly the quality of life of patients and tissue hypoxia is associated with ulceration. Transcutaneous oxygen pressure (tcPO2) provides information on the delivery of oxygen through the microvascular circulation and measuring tcPO2 might detect values at which patients with post-thrombotic syndrome might ulcerate. The aim of our study is to determine tcPO2 in post-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, even a single measurement at the site of greatest skin change was statistically significant, as shown in this study. Recently, TcPO 2 was also studied in post-thrombotic syndrome (PTS) by Cuen-Ojeda et al [ 16 ], who found low TcPO 2 levels in severe cases of PTS.…”
Section: Discussionmentioning
confidence: 99%
“…However, even a single measurement at the site of greatest skin change was statistically significant, as shown in this study. Recently, TcPO 2 was also studied in post-thrombotic syndrome (PTS) by Cuen-Ojeda et al [ 16 ], who found low TcPO 2 levels in severe cases of PTS.…”
Section: Discussionmentioning
confidence: 99%